2009
DOI: 10.9775/kvfd.2011.4438
|View full text |Cite
|
Sign up to set email alerts
|

A Study on The Microbiological Growth and Microbiological Quality in The Cooked Doner Kebabs

Abstract: Bu çalışma piyasada hızlı yemek restaurantlarda satışa sunulan pişmiş haldeki dönerlerin mikrobiyolojik kalitesini ortaya koymak ve pişme sonrası bekleme sırasında mikroorganizma sayısındaki değişimleri incelemek amacıyla gerçekleştirilmiştir. Öncelikli olarak İstanbul'da Avcılar bölgesindeki 20 farklı satış noktasından toplam 30 adet döner örneği toplanmış ve mikrobiyolojik analizleri yapılmıştır. Daha sonra üç ayrı işletmeden alınan dönerler oda sıcaklığında bekletilerek belli aralıklarla mikroorganizma sayı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Odu and Akano () observed that the coliform counts of 12 döner kebabs obtained from Nigeria had ranged between 1.9 × 10 3 and 9.4 × 10 5 cfu/g. Bostan et al () who studied the microbial quality of cooked döner kebabs sold in Istanbul, Turkey reported that the E. coli counts of döner kebabs had changed between the <10 1 and 10 4 cfu/g. In addition, Küpeli Gençer and Kaya () stated that the coliform and E. coli counts of döner kebabs sold in Erzurum, Turkey were between <1 and 4.2 log cfu/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Odu and Akano () observed that the coliform counts of 12 döner kebabs obtained from Nigeria had ranged between 1.9 × 10 3 and 9.4 × 10 5 cfu/g. Bostan et al () who studied the microbial quality of cooked döner kebabs sold in Istanbul, Turkey reported that the E. coli counts of döner kebabs had changed between the <10 1 and 10 4 cfu/g. In addition, Küpeli Gençer and Kaya () stated that the coliform and E. coli counts of döner kebabs sold in Erzurum, Turkey were between <1 and 4.2 log cfu/g, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Previous researches stated that, theoretically cooked döner kebabs can be recognized as microbiologically safe, but in practical life market surveys revealed that döner kebabs have hygiene problems and if they are not sold immediately after they are produced, they can cause risks for public health. Due to the heat that is applied during the cooking process, most of the bacterial load of döner kebab decreases; but, remained bacteria can grow during storage and can cause spoilage, infection or toxication (Bostan et al, ; Kayışoğlu et al, ). In the current study, the effect of different packaging methods, microwave application and storage time on microbial quality changes of döner kebabs were revealed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, it is reported that döner purchased from local fast-food units had an average total aerobic bacteria count of 10 4 -10 5 CFU/g (21)(22)(23)(24)(25). It is remarkable that the effects of storage, combined with low storage temperature and packaging conditions, increased with time and reduced the microbial count.…”
Section: Discussionmentioning
confidence: 99%